2021
DOI: 10.1007/s10162-020-00783-y
|View full text |Cite
|
Sign up to set email alerts
|

Using Interleaved Stimulation to Measure the Size and Selectivity of the Sustained Phase-Locked Neural Response to Cochlear Implant Stimulation

Abstract: We measured the sustained neural response to electrical stimulation by a cochlear implant (CI). To do so, we interleaved two stimuli with frequencies F1 and F2 Hz and recorded a neural distortion response (NDR) at F2-F1 Hz. We show that, because any one time point contains only the F1 or F2 stimulus, the instantaneous nonlinearities typical of electrical artefact should not produce distortion at this frequency. However, if the stimulus is smoothed, such as by charge integration at the nerve membrane, subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 65 publications
(32 reference statements)
3
18
0
Order By: Relevance
“…This ensured there would be two electrodes at each temporal bone (P9/P10 and the two flat electrodes) in case one of these electrodes became noisy during a recording session. All neural potentialsboth for the FFR and ACC-are reported and analysed on a decibel scale, consistent with previous reports from our group [21,23,[30][31][32][33]. This ensures that the size of the difference between two conditions is not affected by factors that influence the overall gain between the neural generator and neural response, such as between-subject differences in the distance or orientation of neural generators relative to the recording electrodes.…”
Section: Paradigm Stimuli and Stimulating Equipmentsupporting
confidence: 80%
See 1 more Smart Citation
“…This ensured there would be two electrodes at each temporal bone (P9/P10 and the two flat electrodes) in case one of these electrodes became noisy during a recording session. All neural potentialsboth for the FFR and ACC-are reported and analysed on a decibel scale, consistent with previous reports from our group [21,23,[30][31][32][33]. This ensures that the size of the difference between two conditions is not affected by factors that influence the overall gain between the neural generator and neural response, such as between-subject differences in the distance or orientation of neural generators relative to the recording electrodes.…”
Section: Paradigm Stimuli and Stimulating Equipmentsupporting
confidence: 80%
“…All recordings were obtained using an 8-electrode Bio-Semi Hyper Rate system [21,30] sampling at 32 kHz with a 24-bit resolution. We placed pin electrodes via the cap at locations P9, P10, Iz, Cz, Fz and Fpz, and flat electrodes on the left and right mastoids.…”
Section: Paradigm Stimuli and Stimulating Equipmentmentioning
confidence: 99%
“…The effect of this inter-phase gap (IPG) on the ECAP was previously shown to be positively correlated with neural survival in guinea pigs (Prado-Guitierrez et al 2006;Ramekers et al 2014). Significant across-electrode differences have also been observed in EEG measures including the electrically evoked auditory steady-state response (Gransier et al 2020) and the neural distortion response (Carlyon et al 2021), both of which reflect phase-locked neural activity in the auditory thalamus and/or cortex. Mathew et al (2017) reported a cortical analogue of electrode discrimination (Fig.…”
Section: Across-electrode Variations In the Electrode-neuron Interfacementioning
confidence: 99%
“…Further complications arise from the use of anaesthesia in the physiological studies (Chung et al 2016), from the use of different outcome measures, such as behavioural judgements for humans and single-unit recordings for animals, and from between-species differences in the anatomy of the auditory nerve (Rattay et al 2013). Recently, researchers have begun to bridge this gap by combining physiological experiments with threshold and supra-threshold behavioural measures using animals (Kadner and Scheich 2000;Vollmer et al 2001;Pfingst et al 2011;Benovitski et al 2014;King et al 2016;Rosskothen-Kuhl et al 2021), and by developing electrophysiological measures of stimulus discrimination and cortical selectivity in humans that may in principle be applied to animal studies (Mathew et al 2017(Mathew et al , 2018Presacco and Middlebrooks 2018;Carlyon et al 2021).…”
Section: The Neural Basis For Success and Failure Of Proposed Innovationsmentioning
confidence: 99%
“…We recently described a new way of measuring the sustained neural response to high-rate AM pulse trains applied to one or more CI electrodes. The Alternating Low-Frequency Interleaved Stimulation (ALFIES) method [ 8 ] interleaves the pulses from two sinusoidally amplitude-modulated pulse trains, having identical pulse rates and different modulation frequencies of F1 and F2 Hz ( Fig. 1a ).…”
Section: Introductionmentioning
confidence: 99%